Land change-based forest management scenario in the typology of island clusters in Maluku Province, Indonesia - Patrich papilaya; I NENGAH SURATI JAYA; TEDDY RUSOLONO; NINING PUSPANINGSIH (Society for Indonesian Biodiversity, 2021)
Abstract. Papilaya PPE, Jaya INS, Rusolono T, Puspaningsih N. 2021. Land change-based forest management scenario in the typology of island clusters in Maluku Province, Indonesia. Biodiversitas 22: 3756-3763. This study aims to describe the development of forest area utilization scenarios with biophysical, social and spatial trend approaches. In this study, spatial trends were identified using forest and land cover maps from 2000 to 2018, and the methods used include change detection, spatial trend and overlay. The study was designed using forest cover scenarios along with spatial trends and social and biophysical approaches. The results of the 5 typologies of island clusters analysis showed that forest degradation has occurred in an area of ± 77102 ha between 2000 and 2018 with an average of 4283.4 ha/year. Furthermore, Total Land Cover Loss at the location of the five island cluster typology for 18 years was found to be ± 422805 Ha with an average of ± 23489.06 ha/year. The land capability was categorized into 3 classes. Therefore, the five spatial trends were known to form in the typology of five island clusters with different directions and magnitudes.